STRESS-DISTRIBUTION IN SHRINK FIT WITH ELASTIC-PLASTIC HUB EXHIBITING VARIABLE THICKNESS - GUVEN, U (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
The state of plane stress in shrink fit with an elastic-plastic hub exhibiting variable thickness is studied. The thickness of the hub is assumed to vary exponentially with a general power of the radial distance from the inner boundary of the hub. The analysis is based on Tresca's yield condition, its associated flow rule and linear strain-hardening. Closed-form solutions are obtained in terms of confluent hypergeometric functions.
Keywords: Engineering; Mechanics